The feasibility of shockwave lithotripsy for treating solitary, lower calyceal stones over 1 cm in size - Kim, Tae Beom; Lee, Sang Cheol; Kim, Khae Hawn; Jung, Han; Yoon, Sang Jin; Oh, Jin Kyu (Canadian Urological Association Journal, 2013)
Introduction: Recently, few studies were reported about the treatment of large, solitary, renal calculi between shockwave lithotripsy (SWL) and percutaneous nephrolithotomy (PNL). We assess the feasibility of SWL for managing solitary, lower calyceal stones over 1 cm by comparing the results of lower pole calculi treatment between patients that underwent SWL or PNL. Methods: We retrospectively reviewed clinical data for patients who had undergone PNL or SWL due to lower calyceal stones over 1 cm. Group 1 consisted of patients who underwent SWL to treat lower pole renal calculi from 2010 to 2011. Group 2 included patients who underwent PNL to manage lower pole renal calculi from 2008 to 2009. We compared patient age, gender, stone size, comorbidities, postoperative complications, additional interventions and anatomical parameters between the two groups. Results: A total of 55 patients were enrolled in this study. The mean ages (±SD) of groups 1 (n = 33) and 2 (n = 22) were 55.1 (±13.0) and 50.0 (±10.6) years (p = 0.133) and mean stone sizes were 1.6 (±0.7) and 1.9 (±0.8) cm (p = 0.135), respectively. There were no significant differences in gender distribution, comorbidities or stone laterality between the two groups. No significant differences in various parameters were observed between patients with stones 1 to 2 cm and ones with stones 2 cm or larger. Conclusions: Our results demonstrated that SWL is a safe, feasible treatment for solitary, lower calyceal stones over 1 cm.